English around the world : an introduction - Schneider, Edgar W. (Edgar Werner), 1954- (New York : Cambridge University Press, 2020)
"The global spread of English has had widespread linguistic, social, and cultural implications, affecting the lives of millions of people around the world. This textbook provides a lively and accessible introduction to world Englishes, describing varieties used in countries as broad-ranging as America, Jamaica, Australia, Africa, and Asia, and setting them within their historical and social contexts. Students are guided through the material with chapter previews and summaries, maps, timelines, lists of key terms, discussion questions and exercises, and a comprehensive glossary, helping them to understand, analyze, and compare different varieties of English, and apply descriptive terminology. The book is accompanied by a useful website, containing textual and audio examples of the varieties introduced in the text, and links to related sources of interest. Providing essential knowledge and skills for those embarking on the study of world Englishes, this book has become the leading introduction to the subject"--
1. Introduction -- 2. Basic notions -- 3. Historical background -- 4. Language crossing an ocean: Old World and New World -- 5. Settlers and locals: Southern Hemisphere Englishes, transported and newly born -- 6. Missionaries, merchants, and more: English is useful, English is ours -- 7. Language development: a general perspective -- 8. Issues and attitudes -- 9. Conclusion -- Appendixes -- Glossary -- References -- Index.
Includes bibliographical references and index.
ENH
Keywords: English language -- Variation -- Foreign countries; English language -- Variation -- English-speaking countries; English language